Analysis of Public Services Quality in The Tourism Sector: The Case Study of South Garut West Java Province - Asep Dadang (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
Public services in the tourism sector are one of the most important parts to support the increase in the Human Development Index (HDI) in the economic sector. This requires quality services based on the government's development strategy through public policies that are linked to regional potential, especially the tourism potential of the South Garut area. Based on the results of research with a qualitative approach that the tourism potential of South Garut, both coastal and mountainous areas, is very potential and really needs the attention of all parties, especially the government to make public policies in the tourism sector.